Analysis of the Effect of Brand Equity Elements on Brand Loyalty through Brand Trust on Instant Noodle Products of Local and International Brand on Generation Z in Solo Raya - Windi Nur Azizah; Moechammad Nasir (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study primarily aims to examine the impact of brand equity components on brand loyalty, with brand trust functioning as a mediating variable, within the context of local and international instant noodle brands consumed by Generation Z in the Solo Raya region. A total of 250 respondents were purposively selected based on predetermined criteria, particularly those who regularly purchase or consume both local (Indomie) and international (Samyang) instant noodle brands. Data were collected using a structured questionnaire based on a Likert scale, and analyzed through Partial Least Squares (PLS) modeling utilizing SMARTPLS software version 3.2.9. The analysis included both measurement and structural model evaluations. The results revealed that Brand Association, Brand Awareness, and Perceived Quality all have a positive and statistically significant influence on Brand Trust for both brands. Moreover, among all variables, Perceived Quality was the only factor consistently demonstrating a significant effect on Brand Loyalty. In contrast, the direct impact of Brand Trust on Brand Loyalty was found to be statistically insignificant. Nevertheless, Brand Trust was identified as an essential mediating construct in fostering Brand Loyalty, although its direct effect may not always be substantial.